Ecological Folklore "I Swarnangkara" and Pramoedya Ananta Toer's View in The Perspective of Realism-Socialist Literature - Dwiyani, Ni Kadek; Swandi, I Wayan; Karja, I Wayan; Bayu Pramana, I Made (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2025)
Ecological folklore is a part of literature that is widely developed by raising environmental themes through theme responses and moral messages conveyed as an effort to save the environment. One example of ecological literature in the form of Balinese folklore that also tends to convey character education values to save the forest is Balinese oral literature entitled "I Swarnangkara". The purpose of the study is to examine the existence of oral literature "I Swarnangkara" in Pramoedya Ananta Toer's view in the perspective of Socialist Realist Literature. The method used is descriptive qualitative to facilitate the delivery of the results of the analysis elaborated with the theory of Ecological Literature and Socialist Realist Literature. The object of the research is the oral literature "I Swarnangkara" which represents the message of saving the forest by a young man who grew up in Watukaru Village, precisely in Watukaru forest in Wongaya Gede Village, Tabanan Regency. The results show that the existence of oral literature "I Swarnangkara" contains social realist values that highlight efforts to save the forest environment as a strategy to balance the role of humans and nature for survival. The existence of ecological literature "I Swarnangkara" in the perspective of Social Realist Literature shows that oral literature can function as an educational medium to foster responsibility in protecting nature, especially forests which are the axis and source of oxygen for the world.